Rat ventral prostate xanthine oxidase bioactivation of ethanol to acetaldehyde and 1-hydroxyethyl free radicals: Analysis of its potential role in heavy alcohol drinking tumor-promoting effects - Castro, Gerardo Daniel (2001)
The ability of the ventral prostate cytosolic fractions to biotransform ethanol to acetaldehyde and 1‐hydroxyethyl (1HEt) radicals was tested. Acetaldehyde formation was determined by GC‐FID analysis in the head space of incubation mixtures. 1HEt was determined by spin trapping with PBN followed by extraction, silylation of the adduct and GC‐MS of the product. Prostate cytosol was able to biotransform ethanol to acetaldehyde in the presence of NADH, hypoxanthine, xanthine, caffeine, theobromine, theophylline, and 1,7‐dimethylxanthine but not in the presence of N‐methylnicotinamide. All these biotransformations were inhibited by allopurinol and were sensitive to heating for 5 min at 100°C. The biotransformation of ethanol to acetaldehyde in the presence of purines as cosubstrates was accompanied by the formation of hydroxyl and 1HEt radicals as detected by GC‐MS, and the process was inhibited by allopurinol. Results suggest that prostate cytosolic xanthine oxidase is able to bioactivate ethanol to acetaldehyde and free radicals. The potential of these processes to be involved in tumor‐promoting effects of heavy alcohol drinking in conjunction with high meat and/or purines consumption is analyzed. Multifactorial epidemiological studies considering that possibility might be convenient.